(untitled) (EU and comparative law issues and challenges series (ECLIC), 2022)
The main principle of sustainability means being able to meet the needs of today’s society without compromising the ability of future generations to meet their own needs. Sustainable development implies the interdependence of its main components: society, economy, and ecology. The prosperity of a society depends on economic progress and the development of new technologies, but in a way that the natural environment is protected and preserved. This concept is inextricably linked to the concept of ecology and, consequently, to all types of transport, given that transport is considered one of the main pollutants of the ecosystem. Due to its rapid development through history, and as the youngest and safest type of transport, air transport is particularly subjected to the environmental impact assessment. At the same time, air transport affects the global economy due to its connection with other sectors, which in turn enables faster mobility of people, services, and goods. This was especially evident with the increased need for faster medical supplies and protective equipment delivery during the COVID-19 pandemic. The European Union’s transport policy is geared towards sustainable development by linking all environmental and social goals in a balanced way. Considering the negative long-term impact of COVID-19 on the air transportation sector, the question posed in this paper is whether this can be done in an appropriate way. As part of the European Green Deal, the “Fit for 55” package is a set of proposals to revise and update EU legislation with the purpose of introducing new initiatives regarding the climate goals agreed by the Council and the European Parliament. Regarding air transport, the emphasis is on contributing to reducing CO2 emissions and noise pollution and their impact on other sectors and competitiveness. The EU Commission White Paper: “Roadmap to a Single European Transport Area – Towards a competitive and resource efficient transport system” emphasizes that the EU aviation industry should become a frontrunner in the use of low-carbon fuels to reach the set targets, as well as that the majority of medium-distance passenger transport should go by rail by 2050. There are also initiatives that aviation taxes should subsidize high-speed rail (HSR), which potentially may cause a decrease in the air transport and benefit an increase the rail transport. The paper will also address the questions as to whether existing legislation, measures, and proposals are appropriate, considering that aviation is one of the industry sectors that is most affected by COVID-19 and could be most affected by the “Fit for 55” package, as well what impact this duopoly might have on the market for travel served by air transport. Does really “Fit for 55” fit air transport?